Policy Coordination in the European Monetary System : Occa Paper 61. (Occasional Papers; Occasional Paper ;, 1988)
This chapter discusses various aspects of policy coordination in the European Monetary System (EMS). The purpose of the first paper in this chapter is to provide a survey of the process of European monetary integration, with focus on the EMS, its purposes, evolution, and the experience gathered since its establishment in early 1979. In its present stage of evolution, the EMS has developed a body of general institutional procedures to promote consistency among the policies and objectives of participating countries. The search for consistency inevitably gives rise to consequent constraints, such as those implicit in the specific rules on exchange rate and international reserve management that characterize the exchange rate mechanism (ERM). By drawing on an analysis of the role of monetary policy in balance of payments adjustment under different monetary systems and exchange rate arrangements, the second paper focuses on the crucial issues involved when an attempt is made to set rules for monetary policy coordination in a system of fixed but adjustable exchange rates such as the EMS.